Partisipasi Masyarakat Tariqah Pada Penyelenggaraan Pendidikan Di Yayasan Lpmnu Talang Prigen Pasuruan - Akhmad Sirojuddin (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2018)
Objective research that will produce research findings that can be used or acted upon by elements related to the investigation. In this case the researchers conducted a regional study in the Tariqah village of Talang Prigen Pasuruan village on matters relating to Jam'iyah's participation in education. In this study the researchers obtained research findings that (1) the participation of the Tariqah community as a facilitator in providing educational services through out-of-school programs, (2) the participation of the Tariqah community as a motivator in the NU Ma'arif education institution in the area, 3) Tariqah community participation as partners in the success of education in the area. This finding is based on the condition of people who have an economic, social and educational background. This research hopes to release education in the red region.